Periodontal disease in sheep and cattle: understanding dental health in past animal populations - Holmes, M; Thomas, R; Hamerow, H (Elsevier, 2021)
Objective To provide a comparative baseline for future studies of oral pathology in domestic livestock and to better understand connections between lesion prevalence and biological context in past animal populations. Materials Over 1600 sheep and cattle mandibles recovered from archaeological sites in England between 500 and 1300 CE. Methods A comprehensive investigation of periodontal disease was conducted based on four characteristics: dental calculus; periosteal new bone formation; alveolar recession; and ante-mortem tooth loss. The anatomical position and severity of these lesions were quantified and correlated against the age of each individual. Results Two types of periosteal new bone formation were recognized: one in the growing mandibles of young animals, the other in older animals and associated with disease. The incidence of calculus and alveolar recession increase with age. Correlations exist between calculus, alveolar recession and periosteal new bone formation. Disruption caused by the eruption of the P4 is also implied as a contributory factor to the onset of periodontal disease. Conclusions When interpreting periodontal disease in zooarchaeological collections it is vital to consider the effect of age as well as environmental and genetic factors. Significance This is the first comprehensive zooarchaeological study to investigate the effect of age on periodontal disease. It provides a better understanding of the frequency and presentation of periodontal disease as a baseline for future studies. Limitations Cattle mandibles are under-represented due to poor survival. Ideally, radiographs of mandibles with ante-mortem tooth loss would be taken, but this was not possible. Suggestions for further research The role of genetic factors, diet and environment needs to be better understood.